The Possible Nephroprotective Effect of Roflumilast Ameliorating Glycerol -Induced Myoglobinuric Acute Renal Injury in Rabbits Model - Mukhallad A. Ramadhan1 ; Haider F. Al-Saedi2 ;Ghufran L. Ismaeel2 ; Uday Abdul-Reda Hussein3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
urther leads to tissue necrosis and inflammation. While, roflumilast N-oxide is an active metabolite ofroflumilast that rising the cyclic adenosine-3?, 5?-monophosphate by inhibiting PDE4.Thirty rabbits were divided into three groups, control group was received normal saline intra-muscularly anddrived from water for eighteen hours before. Second group was received a single dose glycerol injected intramuscularly after drived from water for eighteen hours .Third group was received roflumilast intraperitonealdaily for three days after received a single dose of glycerol .All animals were sacrificed after 72 hour, and then blood collected by cardiac puncture for evaluation thechanges in the levels of renal function tests and histopathological study of rabbit’s kidneys tissues areevaluated evaluation and scoring the changes of tested agents. The numerical data are expressed as means ±standard error means and analyzed by using SPSS version 20.The results of the levels serum urea and creatinine found to be significantly reduced by roflumilast usingANOVA test. Besides, the histopathological changes showed ameliorative effects of roflumilast in comparedto glycerol group. From this study, one could be concluded the protective effect of roflumilast in case ofrenal failure induction by glycerol.